Study on crack propagation in layered rock under the three-point bending conditions - Yang, Yingming; Ma, Zhibo; Zhang, Weilong; Liu, Gang; Zhang, Peng (Frontiers in Earth Science, 2023)
The pattern of layered rock crack propagation in mining and geotechnical engineering directly influences the production efficient of coal mines and the safety of workers. To reveal the characteristics of crack propagation in layered rock, the three-point bending experiment and numerical investigation were carried out to study the crack propagation process of single sandstone samples, sandstone-sandstone-sandstone combined samples, and sandstone-mudstone-sandstone combined samples. Using digital speckle correlation methods (DSCM) and acoustic emission (AE) techniques, the crack propagation process of the specimens was examined. The results show that the main factors affecting crack propagation include rock layer strength, bedding plane strength, and the position of pre-existing fractures. The presence of the bedding plane hinders the propagation of cracks, and when the bedding plane’s strength decreases, cracks that originated from the bedding plane spread horizontally along it. The weakening of the intermediate rock layer strength of the combined samples can lead to the initiation of microcracks within it earlier than macroscopic cracks, allowing many options for the initiation and propagation of following cracks. Meanwhile, the load-time curves of the combined samples during the experiment displays a double-peak characteristic. Furthermore, the presence of pre-existing fractures inside the layered rock might result in the unpredictability of the crack starting point and subsequently influence the crack propagation course.